1987
DOI: 10.1002/1097-0142(19871101)60:9<2284::aid-cncr2820600930>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Cancer of the pancreas: 50 years of surgery

Abstract: The course of 196 patients with proven carcinoma of the pancreas seen at Yale New Haven Hospital from 1972 to 1982 was analyzed. Only 73% of the patients were preoperatively expected to have cancer of the pancreas. The patients who underwent resection had the longest mean survival but also the longest total hospital stay. Twenty-seven patients survived 1 year or more, but nonresected patients constituted 81.5% of this group. The only 5-year survivor did not undergo resection. Forty-seven percent of patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
202
0
20

Year Published

1994
1994
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 572 publications
(223 citation statements)
references
References 152 publications
1
202
0
20
Order By: Relevance
“…Bramhall et al (1995) reported an overall 5YSR in a series of 13 560 patients with pancreatic cancer of 50.2% with only 2.6% undergoing resection (5YSR of 5.5%) (Bramhall et al, 1995). Gudjonsson (1987) reported similar results in an overview of the published literature and an analysis of patients from his own institution. Traditionally therefore, most clinicians have viewed pancreatic cancer in a nihilistic manner and have been only prepared to offer supportive care (Douglass, 1987).…”
Section: Discussionmentioning
confidence: 54%
“…Bramhall et al (1995) reported an overall 5YSR in a series of 13 560 patients with pancreatic cancer of 50.2% with only 2.6% undergoing resection (5YSR of 5.5%) (Bramhall et al, 1995). Gudjonsson (1987) reported similar results in an overview of the published literature and an analysis of patients from his own institution. Traditionally therefore, most clinicians have viewed pancreatic cancer in a nihilistic manner and have been only prepared to offer supportive care (Douglass, 1987).…”
Section: Discussionmentioning
confidence: 54%
“…Once pancreatic cancer is clinically evident, it progresses at a rapid rate, and metastasis has usually occurred at the time of diagnosis. Consequently, many patients are not resectable at presentation, and the overall resection rate is often less than 30% (Gudjonsson 1987;Bomman et al, 1994). The mechanisms that regulate this aggressive growth behaviour in pancreatic cancer are not at all clear.…”
mentioning
confidence: 99%
“…It binds to a specific membrane receptor denominated uPA receptor (uPAR Pancreatic cancer has one of the poorest prognoses of all gastrointestinal malignancies, being the fourth or fifth leading cause of cancer-related deaths in Western industrialized countries (Bomman et al, 1994). Gudjonsson (1987), in his classical review of 37 000 patients with pancreatic cancer, demonstrated an overall survival rate of 0.4% and a median survival time of 5 months after the diagnosis was established. Once pancreatic cancer is clinically evident, it progresses at a rapid rate, and metastasis has usually occurred at the time of diagnosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…T h e percentage of surgically resectable patients is less than 2 0 %j and of those resected the m edian survival is only 9-15 m onths [23 3] while 5-year survival rates are less than 5% [4,5].…”
Section: Introductionmentioning
confidence: 99%